Altered Motor Unit Discharge Coherence in Paretic Muscles of Stroke Survivors - Dai, Chenyun; Suresh, Nina L.; Suresh, Aneesha K.; Rymer, William Zev; Hu, Xiaogang (Frontiers in Neurology, 2017)
After a cerebral stroke, a series of changes at the supraspinal and spinal nervous system can alter the control of muscle activation, leading to persistent motor impairment. However, the relative contribution of these different levels of the nervous system to impaired muscle activation is not well understood. The coherence of motor unit (MU) spike trains is considered to partly reflect activities of higher level control, with different frequency band representing different levels of control. Accordingly, the objective of this study was to quantify the different sources of contribution to altered muscle activation. We examined the coherence of MU spike trains decomposed from surface electromyogram (sEMG) of the first dorsal interosseous (FDI) muscle on both paretic and contralateral sides of 14 hemispheric stroke survivors. sEMG were obtained over a range of force contraction levels at 40%, 50% and 60% of maximum voluntary contraction. Our results showed that MU coherence increased significantly in delta (1-4 Hz), alpha (8-12 Hz) and beta (15-30 Hz) bands on the affected side compared with the contralateral side, but was maintained at the same level in the gamma (30-60 Hz) band. Additionally, no significant alteration was observed across medium-high force levels (40-60%). These results indicated that the common synaptic input to motor neurons increased on the paretic side, and the increased common input can originate from changes at multiple levels, including spinal and supraspinal levels following a stroke. All these changes can contribute to impaired activation of affected muscles in stroke survivors. Our findings also provide evidence regarding the different origins of impaired muscle activation post-stroke.